2014
DOI: 10.14254/2071-789x.2014/7-4/4
|View full text |Cite
|
Sign up to set email alerts
|

Interconnections between Public Indebtedness and Inflation in Contemporary Economies

Abstract: This paper aims to analyze the specific interconnections established between public indebtedness and inflation, both from the perspective of considering inflation as a result of public borrowing and of voluntarily promoting inflation to reduce the (real) value of public debt and to ease its burden. It identifies the channels through which these effects are occurring, it determines the conditions of their manifestation and evaluates their relevance for different (developed and developing) contemporary economies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…The study concluded that regardless of policies followed by the monetary authorities, persistent and growing borrowings by a government would eventually produce inflation. Bleaney (1996), Bilan and Roman (2014), Nguyen (2015), and Nastansky and Strohe (2015) further argue for a positive relationship between public debt and inflation, while Wheeler (1999), Taghavi (2000), and Essien et al (2016), on the other hand, argued for a negative relationship between these variables. There is a dearth in literature on the negative relationship between public debt and inflation.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The study concluded that regardless of policies followed by the monetary authorities, persistent and growing borrowings by a government would eventually produce inflation. Bleaney (1996), Bilan and Roman (2014), Nguyen (2015), and Nastansky and Strohe (2015) further argue for a positive relationship between public debt and inflation, while Wheeler (1999), Taghavi (2000), and Essien et al (2016), on the other hand, argued for a negative relationship between these variables. There is a dearth in literature on the negative relationship between public debt and inflation.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Kwon et al. (2009), Reinhart and Rogoff (2010), and Bilan and Roman (2014) do not find the inflationary effect of public debt in developed countries although it holds in developing countries. Similarly, governance reduces inflation in developed countries.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Unlike the above-mentioned studies, Kwon et al (2009), Reinhart and Rogoff (2010), and Bilan and Roman (2014) provide empirical evidence to show that the inflationary effect of public debt exists in developing countries, not in developed countries. The findings in Kwon et al (2009) show that the inflationary effect of public debt holds strongly in highly indebted developing countries and weakly in other developing countries but does not hold in developed countries by using the estimators of fixed effects and difference GMM Arellano-Bond for a sample of 71 countries over the period 1962-2004.…”
Section: Introductionmentioning
confidence: 95%
“…The studies by Cardoso and Fishlow (1990), Leeper (1991), Janssen, Nolan, and Thomas (2002), Bildiric and Ersin (2007), Kwon, McFarlane, and Robinson (2006), Karakaplan (2009), Reinhart andRogoff (2010), Faraglia et al (2012), Ahmad, Sheikh, and Tariq (2012), da Veiga, Ferreira-Lopes A, and Sequeira (2016), Ezirim, Amuzie, and Mojekwu (2014), Ngerebo (2014), Bilan and Roman (2014) , Nastansky and Strohe (2015), Nguyen (2015), Ezirim, Amuzie, and Mojekwu (2014), Romero and Marin (2017) and Afonso and Ibraimo (2018) revealed a positive impact of public debt on inflation. On the other hand, a few studies have shown that public debt has a negative impact on inflation.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%